STATISTICS MASTERING PROFILE OF STUDENTS IN BIOLOGY EDUCATION STUDY PROGRAM - Fatmawati, Diani; Fauzi, Ahmad (Unnes Science Education Journal, 2019)
Mastering statistic consepts to be applied in research is crucial competency for Biologi Education students. This research aimed to observe the competency level of Biology Education students in implementing their statistical knowledge. The population of this survey research was the students in seventh semester of Department of Biology Education, Faculty of Teacher Training and Education, Universitty of Muhammadiyah Malang. Meanwhile, the sample were 41 students which comprised of 31 females and ten males. The quantitative data gained was analyzed descriptively to observe the statistical mastering concept of students in general. In addition, one-way ANOVA test was also conducted to determine whether there was a significant difference among students with difference academic levels in mastering statistical concepts. The findings showed that the statistical competencies of Biology Education students were low. Furthermore, the students with low, fair, and high academic abilities had no significant difference in mastering statistical concepts. Based on the findings, it is a demanding task for lecturers to creat the most proper learning design in their lectures which boost students’ self-eficacy as well as their motivation and positive attitude so that it will ease them to be engaged in statistical learning.